Amplify-and-forward based two-way relay ARQ system with relay combination - Luo, Sheng (2015)
In this letter, we propose an automatic repeat request (ARQ) protocol for the amplify-and-forward (AF) based two-way relay system. In the proposed ARQ scheme, the ARQ process is carried out by the relay node (RN). We assume that the RN has one buffer and it can store the signals received. With the help of the buffer, the RN can combine the signals received from different slots and choose to transmit or receive adaptively. Two combining methods, namely the maximal sum signal-to-noise ratio combining (MSC) scheme and the maximal minimum signal-to-noise ratio combining (MMC) scheme, are proposed, which are shown to improve the reliability of the relaying systems.